Tumbuhnya Solidaritas Sosial Di Tengah Banjir Bandang Semarang Tahun 1990 - Harini, Okti Ria; Wijayati, Putri Agus (Universitas Pendidikan Ganesha, 2025)
This article aims to revisit the emergence of social awareness among the people of Semarang during the flood disaster of 1990. That year, the flood was caused by both natural and non-natural factors. One of the triggers was heavy rainfall, which caused the Kaligarang River to overflow and flood the areas of Sampangan, Simongan, and Bongsari. These three areas suffered significant losses, both material and non-material. In addition, the flood, categorized as a large-scale disaster, or as the community referred to it, a